The Compositional Styles Of A Legendary Theatrical Music Composer: Hubert Ogunde - Mary Taiwo Omotosho (Accelerando: BJMD)
Studies on Hubert Ogunde have focused more on dramaturgy with little attention on his music compositions. This study traces the musical background of Ogunde, the pioneer of Yoruba traditional theatrical music, in order to discover the source of his musical flair and taste, in identifying the compositional styles employed in his theatrical music. It analyses his songs in ascertaining the uniqueness of his styles. The study of Hubert Ogunde’s compositional styles rests upon his creativity and depth of imaginative explorations, i. e. rests upon achieving the set objectives. Accordingly, Euba’s theory of creative ethnomusicology (Euba 2000) has been adapted for this study, Methodology includes discography of 40 soundtracks, interviews, relevant literature and internet. Data collected were transcribed and analysed within the ethnomusicological framework. The results showed that Ogunde’s musical background was enhanced by self determination to make a living through theatre. His first exposure to music began from his childhood experience of the alarinjo theatre. The study identifies three styles exhibited by the composer. Two are adoptions of existing musical styles (folk and highlife) while the third is his innovation which we have termed, High-Chant. The new style was revealed through frequent chanting, speech-singing and syncopation in his songs. In conclusion, Ogunde’s music is essential in understanding the theatrical music in Nigeria. His didactic music, uniquely interwoven in strict traditional African styles and Western variants, enhanced a new theatrical dimension in Nigeria. That Ogunde was able to creatively explore varying compositional styles in Yoruba theatre and principally formed the basis for the theatre and film production, shows that his music was, and is evergreen relevant to the society.